PENGUJIAN PUTARAN THRESHER TERHADAP PEROLEHAN PEMBRONDOLAN TANDAN BUAH REBUS (TBR) PABRIK KELAPA SAWIT (PKS) DOLOK ILIR PTPN IV REGIONAL II - Aisyah, Siti; Faisal, Busrizal; Muhammad Jumadil Alamsyah (Jurnal Agro Fabrica, 2025)
This study aimed to determine the optimal rotational speed of the thresher in improving the stripping efficiency of sterilized oil palm fruit bunches. The thresher functions as a rotating drum that separates loose fruits from the bunch by lifting, striking, and pushing empty bunches toward the empty bunch conveyor, while the loose fruits fall through the drum grid and are conveyed to the digester. The research was conducted using a quantitative descriptive method at PT Perkebunan Nusantara IV Regional II Dolok Ilir Palm Oil Mill, Dolok Batu Nanggar District, Simalungun Regency, North Sumatra Province. Data collection at the thresher station was carried out for 20 days, from May 5 to May 24, 2025, including measurements of thresher rotational speed, grid spacing, and loose fruit diameter. The results showed that the optimal thresher rotational speed ranged between 23.8 and 23.9 rpm, with an average grid spacing of 4.51 cm and an average loose fruit diameter of 2.67 cm. The standard deviation of measurements was 0.42%, indicating high operational stability. Technically, the correlation between thresher rotational speed and loose fruit diameter was 21.24 rpm, while the technical deviation correlation was 12.24%..